2019
DOI: 10.1519/jsc.0000000000003465
|View full text |Cite
|
Sign up to set email alerts
|

Core Muscle Activation in Three Lower Extremity Exercises With Different Stability Requirements

Abstract: Saeterbakken, AH, Stien, N, Pedersen, H, and Andersen, V. Core muscle activation in three lower extremity exercises with different stability requirements. J Strength Cond Res 36(2): 304-309, 2022-The aim of the study was to compare core muscle surface electromyography (sEMG) during 3-repetition maximum (3RM) and the sEMG amplitude in the turnover from the descending to ascending phase in leg press, free-weight squats, and squats using the Smith machine. Nineteen women with 4.5 (62.0) years of resistance traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
0
15
0
1
Order By: Relevance
“…One of the novel findings of this systematic review was that free-weight exercises (e.g., deadlift, hip-thrust, or back squat) showed the greatest ES muscle activation [38,46]. In this regard, some researchers [74] recommend adding destabilizing bars to free-weight exercises because when used with heavy weights, these bars have been designed to make the lifting action harder.…”
Section: Erector Spinaementioning
confidence: 97%
See 1 more Smart Citation
“…One of the novel findings of this systematic review was that free-weight exercises (e.g., deadlift, hip-thrust, or back squat) showed the greatest ES muscle activation [38,46]. In this regard, some researchers [74] recommend adding destabilizing bars to free-weight exercises because when used with heavy weights, these bars have been designed to make the lifting action harder.…”
Section: Erector Spinaementioning
confidence: 97%
“…All parts of the feet are in contact with the floor. This exercise may vary depending on specific protocols (e.g., back squat on unstable surfaces, on Smith machine, different loads, or half-squat) [28,30,38,44,48,53,69,74,77,83].…”
Section: Back Squatmentioning
confidence: 99%
“…Five studies were rejected directly because the samples included inexperienced participants. All the study participants reported a minimum of six months resistance training experience; this is because the experience time and exercise familiarization variable may significantly affect the muscle activation elicited during an exercise, hence the importance of having a homogeneous and experienced sample [30][31][32][33][34].…”
Section: Search Resultsmentioning
confidence: 99%
“…Therefore, the intensity normalization method should be standardized when comparing several exercises from among the studies in order to achieve conclusive outcomes. For instance, apparently a~70% 1RM intensity normalized as %MVIC might be set as an appropriate intensity for the strength training electromyographic studies [6,12,14,33,34]. Besides the disparities regarding the intensity and the sEMG normalization methods used in the studies included in the review, some other differences were found regarding the methodological process.…”
Section: Methodological Gaps Between the Studiesmentioning
confidence: 99%
See 1 more Smart Citation